The Application of Fiqh Principles in Contemporary Sharia Transactions in The Development of Innovative Products of Islamic Financial Institutions in Indonesia - Zujajatul ‘Ilmi (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2023)
The innovation product in Islamic financial institutions is one of the strategies that has an important role in the midst of a competitive market. Increasing institutional capacity and the availability of diverse and efficient Islamic financial industry products is one of the missions in optimizing the development of Islamic finance. The program to increase the availability and diversity of Islamic financial types available in various products, in Islamic banking institutions and non-Islamic bank financial institutions, including the Islamic capital market, shows that the market share of Islamic financial industry products is still limited when compared to conventional financial products. In Indonesia, all stakeholders of the Islamic financial industry must always synergize and harmonize between sharia economic law and applicable laws and regulations. The Qur'an, Al-Hadith and Ijma' gave birth to the rules of fiqh. The rules of fiqh aim to establish Islamic law in various issues that are new and continue to develop along with the times, especially developments in sharia financial institutions in various kinds of economic transactions or muamalah maliyah. The rules of fiqh are a form of ijtihad. The rule of fiqh is an ease of knowing contemporary laws, especially various kinds of economic problems that do not have much nash sharih (definite postulates) in the Qur'an and al-Hadith. In economic problems that develop in Islamic financial institutions, the rules of fiqh are used to facilitate mastering the problems of furu'iyyah (branches) which are many (countless) and continue to grow